1993
DOI: 10.1037/0033-295x.100.3.460
|View full text |Cite
|
Sign up to set email alerts
|

The perception of natural contour.

Abstract: The observation that natural curves and surfaces are often fractal suggests that people may be sensitive to their statistical properties. The perceptual protocols that underlie discrimination between fractals and between other types of random contour and fractals are examined. Discrimination algorithms that have precisely the same sensitivities as human observers are constructed. These algorithms do not recognize the integrated scale hierarchy intrinsic to fractal form and operate by imposing a metatheory of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…A common answer is that the natural world -and the way it changes over time -is also characterized by pink noise, which suggests that our fractal minds are optimized to process the fractal characteristics of natural scenes (see, for example, [Knill et al 1990]). This hypothesis is supported by the finding that discriminating fractal contours is best for those that have the same (fractal) properties as natural scenes [Gilden et al 1993]. Interestingly, these findings can (tentatively) explain the creation of fractal artwork, and fractal architecture in particular.…”
supporting
confidence: 71%
“…A common answer is that the natural world -and the way it changes over time -is also characterized by pink noise, which suggests that our fractal minds are optimized to process the fractal characteristics of natural scenes (see, for example, [Knill et al 1990]). This hypothesis is supported by the finding that discriminating fractal contours is best for those that have the same (fractal) properties as natural scenes [Gilden et al 1993]. Interestingly, these findings can (tentatively) explain the creation of fractal artwork, and fractal architecture in particular.…”
supporting
confidence: 71%
“…Some authors propose that, because of its fractal nature, the brain is optimized to process the statistical characteristics of natural scenes, which are also found to be governed by 1/f spectra (e.g., Knill, Field, & Kersten, 1990). For instance, Gilden, Schmuckler, and Clayton (1993) found that discriminating fractal contours was best for those sharing (statistical) properties with natural scenes. Consistent with this is the finding that neurons in the V1 area of the brain show a preference for 1/f signals (Yu, Romero, & Lee, 2005).…”
Section: Applying Nature's Fractal Geometry To Architecturementioning
confidence: 99%
“…Aligned with this distinction is whether a process is scale free or governed by a controlling time scale. Fractal noises have a symmetry referred to as self-affinity (Mandelbrot, 1985), and this property entails both the absence of discernible scales and the presence of longrange correlations (see Gilden, Schmuckler, & Clayton, 1993;Mandelbrot, 1983;Maylor, Chater, & Brown, 2001;Schroeder, 1991, and the references therein). The exact sense in which time scales and the range of correlations intertwine will be discussed in detail below.…”
mentioning
confidence: 99%